Mapping of global citizenship research in Indonesia 2011-2025: A bibliometric study - Arpannudin, Iqbal; Estrecho, Gly V; Charismana, Dian Satria; Saputro, Johan Dwi; Alrakhman, Riza; Alvinca, Muhammad Fikri; Cañete, Jhenica (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
This study explores the landscape of global citizenship education (GCE) in Indonesia from 2011 to 2025. Despite being a critical issue closely linked to national values such as Pancasila and religious moderation, the current discourse remains fragmented. Using a bibliometric approach with the Bibliometrix R package and Scopus data, the research maps publication trends, keywords, and collaboration networks. Findings reveal a significant surge in publications since 2019, peaking in 2023, driven by Sustainable Development Goals (SDGs) and national policy shifts. While character education and democracy remain dominant themes, newer topics like digital citizenship and religious moderation are emerging. However, research is heavily concentrated in Javanese teacher-training institutions and lacks global collaboration. Vital gaps include a low integration of ecological issues and a limited interdisciplinary focus. The study concludes that future research must bridge these gaps by prioritising digital literacy and environmental sustainability within the framework of Indonesian citizenship education.